2022
DOI: 10.3389/frhs.2022.957368
|View full text |Cite
|
Sign up to set email alerts
|

“There is always a waitlist”: The experiences of perinatal women randomized to a waitlist condition in a trial evaluating a novel online self-directed intervention for perinatal anxiety

Abstract: BackgroundPregnant and postpartum women are at a heightened risk for the development or worsening of mental health problems, with elevated rates of mood and anxiety disorders noted across studies. Timely access to mental health supports is critical during the perinatal period (spanning pregnancy to 1 year postpartum), to mitigate potential negative impacts on mother and child. In general adult populations, a small body of research has highlighted the association between being waitlisted for mental health servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Across the literature, responses to being placed on a waitlist or being made to wait for treatment varied. Experiences of disappointment and frustration were described in multiple studies (Biringer et al, 2017;Kristjanson et al, 2022;Punton et al, 2022); however, this appeared to be more or less prominent depending on how distressed individuals felt when they were referred (Kristjanson et al, 2022). For example, Dowell et al (2021) conducted surveys and interviews with service users of Piki, a free primary mental health service piloted in Greater Wellington that provides psychological support to 18-25-year-olds experiencing mild to moderate mental distress as part of an evaluative report of the project.…”
Section: Emotional Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the literature, responses to being placed on a waitlist or being made to wait for treatment varied. Experiences of disappointment and frustration were described in multiple studies (Biringer et al, 2017;Kristjanson et al, 2022;Punton et al, 2022); however, this appeared to be more or less prominent depending on how distressed individuals felt when they were referred (Kristjanson et al, 2022). For example, Dowell et al (2021) conducted surveys and interviews with service users of Piki, a free primary mental health service piloted in Greater Wellington that provides psychological support to 18-25-year-olds experiencing mild to moderate mental distress as part of an evaluative report of the project.…”
Section: Emotional Responsesmentioning
confidence: 99%
“…Similarly, Kristjanson et al (2022) interviewed perinatal women with self-reported symptoms of anxiety about their experiences on a waitlist condition for an online intervention in cognitive behavioural therapy. Although many participants expressed disappointment at being waitlisted, some also described feeling relieved that they were on the list to receive support and grateful they would be able to participate in the therapy eventually.…”
Section: Emotional Responsesmentioning
confidence: 99%